FINANCIAL PERFORMANCE AFTER ACQUISITION ON INDONESIA STOCK EXCHANGE - Magdalena Nany; Kristyana Dananti; Sundari, Sundari (International Journal of Social Science, 2024)
The purpose of this study was to determine the difference in financial performance before and after acquisitions. Financial performance was proxied by Current Ratio (CR), Asset Turnover (TATO), Debt to Asset Ratio (DAR), Net Profit Margin (NPM) and Price Earnings Ratio (PER). The research was conducted at the Indonesian Stock Exchange. The object of this research is the company listed on the Indonesia Stock Exchange (IDX) that made the acquisition in 2013-2019. The analysis technique used was Wilcoxon Signed Ranks. Based on the analysis it was found that Total Assets Turnover (TATO) showed difference before and after acquisition. While Current Ratio (CR), Debt to Asset Ratio (DAR) and Price Earnings Ratio (PER) showed no differences before and after acquisition. Net Profit Margin (NPM) showed difference one year before-one year after acquisition and one year before-two years after acquisition.